2016
DOI: 10.7717/peerj.1909
|View full text |Cite
|
Sign up to set email alerts
|

Six-year mortality in a street-recruited cohort of homeless youth in San Francisco, California

Abstract: Objectives. The mortality rate of a street-recruited homeless youth cohort in the United States has not yet been reported. We examined the six-year mortality rate for a cohort of street youth recruited from San Francisco street venues in 2004.Methods. Using data collected from a longitudinal, venue-based sample of street youth 15–24 years of age, we calculated age, race, and gender-adjusted mortality rates.Results. Of a sample of 218 participants, 11 died from enrollment in 2004 to December 31, 2010. The major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 35 publications
2
49
0
1
Order By: Relevance
“…That is, there was no discernible independent effect of SADV in any models accounting for CD symptoms or clinical ascertainment status, although the latter accounted for independent variance regardless of which covariates were presented in the model. However, consistent with previous findings , substance‐related causes comprised the largest proportion of observed deaths and occurred disproportionately among clinical probands and their siblings vis‐á‐vis controls. In light of these findings, we echo previous researchers’ recommendations , that intervention and prevention efforts include SUD treatment within constellation treatment foci including additional psychiatric resources and social services.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…That is, there was no discernible independent effect of SADV in any models accounting for CD symptoms or clinical ascertainment status, although the latter accounted for independent variance regardless of which covariates were presented in the model. However, consistent with previous findings , substance‐related causes comprised the largest proportion of observed deaths and occurred disproportionately among clinical probands and their siblings vis‐á‐vis controls. In light of these findings, we echo previous researchers’ recommendations , that intervention and prevention efforts include SUD treatment within constellation treatment foci including additional psychiatric resources and social services.…”
Section: Discussionsupporting
confidence: 90%
“…Substance‐related and violent causes accounted for the majority of deaths among clinical probands and their siblings, with the substance‐related causes accounting for 32% of deaths among clinical probands (Table ). Results from univariate models confirmed previous findings that male sex , conduct problems and SAD are each associated with increased mortality risk (Table ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…6, 7 Increased exposure to physical endangerment on the street and limited access to resources can predispose to numerous health risks, including violence. 8, 9 One study of homeless Canadian youth found two out of three youth had been a victim of physical violence and one out of three youth had been sexually assaulted while living on the street.…”
Section: Background and Objectivesmentioning
confidence: 99%